Programmable Logic Controller (PLC) Control System on Automatic Shoe Outsole Painting - Sadi, Sumardi Ir.; Mulyati, Sri (Jurnal Teknik, 2024)
This manufacturing company focuses on the production of shoes with the TGN39 brand as the main product it produces. However, in the production process, there are still defective products produced. This research focuses on one of the critical stages in shoe making, namely the screen printing process with a control system using a Programmable Logic Controller (PLC). Based on historical data on Decathlon shoe production in 2019, the number of shoes produced reached 973,198 units, with an average percentage of defective products of 12%. The calculation results show that the Defects Per Million Opportunities (DPMO) value is 241,425, and the sigma value is 3,551. This indicates that the capability of the process that occurs is still below the standard 6 sigma. To identify the causative factors of problems in the production process, a cause-and-effect diagram analysis tool is used. Furthermore, FMEA (Failure Mode and Effect Analysis) analysis is used to determine improvement priorities with the aim of maximizing product quality. Through the proposed improvement measures, such as separation of unused items, arrangement of storage shelves, and regular cleaning activities of the work area, it is expected to improve product quality and minimize defective products. With the implementation of predetermined improvements, the company aims to maximize the quality of its products. Through this approach, it is expected to achieve a level of process capability that meets quality standards, thereby increasing customer satisfaction and brand reputation.